A biblical-theological investigation of the phenomenon of wonders surrounding Moses, Elijah and Jesus - Van der Walt, John Stevens (University of the Free State, 2014)
In the Canon of Scriptures, the phenomenon of miracles/wonders falls into three great Epochs. In the Old Testament there are two Epochs where decisive turning-points marked its course with an intensification of miracles/wonders. First, there are the wonders in the so-called plague narratives and during the “wilderness” in the Exodus tradition. Then, in the ministry of Elijah and Elisha (1 and 2 Kings), came the second Epoch. Both of them (Elijah and Elisha) did miraculous deeds. The third Epoch heralds the ministry of Jesus Christ in the New Testament. This study shows that there are similarities between wonders in the first and the third Epoch, and there are similarities between wonders in the second and the third Epoch, and even in all three. The researcher uses a narrative model which is a combination of existing narrative models, to point out the significance of the similarities between wonders in the three Epochs. Selected aspects used in the model, such as structures, settings, themes and motifs, highlight the fact that there must be a coherent Theological relationship between the three Epochs. Miracles in all three Epochs point to events (forwards and backwards) in the future and in the past, helping the reader to understand that the same God is at work, present, future and past. In all three Epochs the miracle stories give hope to people finding themselves in some kind of oppression. Their hope ultimately lies in God’s presence, shown in his miraculous acts through his agents, Moses and Elijah and his Son, Jesus. The thesis addresses the lack of a detailed examination on the theme of corresponding miracles in the miracle narratives surrounding the figures of Moses, Elijah and Jesus. In order to achieve the goal of a comprehensive narratological study, the model used by the researcher consists of two divisions: A. Preliminary reading and B. Closer investigation. The preliminary reading helps the researcher to get a grip on the narrative as a whole, but also to identify certain aesthetical elements such as structure, settings, themes and motifs, which the authors of the three different Epochs used to craft their miracle stories. The aesthetical “tools” of structure, settings, themes and motifs form the backbone of the study. They point right to the fact that there are similar aspects in miracle stories in the three Epochs. Hence, they show that, in the field of Biblical studies, a thematic approach opens up new possibilities to discuss the coherence between Old Testament and New Testament studies: The theme of “wonders” is one possibility. Hopefully, this dissertation will contribute to a debate (once more) which J.P. Gabler started way back in 1787 and which has been almost forgotten.

In die Bybelse Kanon vind wonderwerke in drie groot Tydperke plaas. Twee spesifieke Tydperke in die Ou Testament word gekenmerk deur ‘n toename in wonders/wonderwerke. Eerstens is daar die wonders/wonderwerke in die sogenaamde plaagnarratiewe en gedurende die “woestyn” van die Eksodustradisie. Die tweede Tydperk breek tydens die bediening van Elia en Elisa (1 en 2 Konings) aan. Beide Elia en Elisa het wonderwerke verrig. Die derde Tydperk kondig die prediking van Jesus Christus in die Nuwe Testament aan. Hierdie studie toon aan dat daar ooreenkomste tussen die wonderwerke in die eerste en derde Tydperke bestaan, en ook tussen die wonderwerke in die tweede en derde Tydperke. Daar is trouens oorkenkomste tussen wonders in al die die Tydperke. Die navorser gebruik ‘n narratiewe model wat ‘n kombinasie is van bestaande narratiewe modelle om die (betekenis of belangrikheid of belang) van die ooreenkomste tussen die die Tydperke aan te dui. Aspekte soos struktuur, ligging, temas en motiewe word in die model aangewend om aan te dui dat daar ‘n koherente Teologiese verband tussen die drie Tydperke is. Wonderwerke in al drie die Tydperke wys op gebeure in die toekoms en die verlede (vorentoe en terug in tyd), en dit help die leser om te begryp dat dieselfde God aan die werk is in die hede, verlede en toekoms. In al drie die Tydperke gee die wonderwerke hoop aan mense wat op een of ander manier onderdruk word. Hulle hoop is te vinde in die teenwoordigheid van God soos gemanifesteer in Sy wonderdade deur sy agente Moses, Elia en Sy Seun, Jesus. Hierdie tesis spreek die gebrek aan ‘n gedetailleerde ondersoek na die tema van ooreenstemmende wonderwerke in die wonderwerknarratiewe van Moses, Elia en Jesus aan. Om die oogmerk van ‘n omvattende narratologiese studie te bereik, bestaan die navorser se model uit twee afdelings: A. Aanvanklike lees-en-interpretasie en B. Nadere ondersoek. Die aanvanklike lees-en-interpretasie help die navorser om ‘n begrip van die narratief as geheel te vorm, maar help ook in die indentifisering van sekere estetiese elemente soos struktuur, plasing, temas en motiewe wat die outeurs in die drie Tydperke gebruik het om hulle wonderwerkstories te skep. Hierdie gemelde estetiese hulpmiddels vorm die basis van hierdie studie. Hulle dui op die feit dat daar ooreenkomste bestaan in die wonderwerknarratiewe van die drie Tydperke. Dit toon weer aan dat ‘n tematiese benadering nuwe moontlikhede in die veld van Bybels- Teplogiese studies meebring om die koherensie tussen Ou en Nuwe Testamente te bespreek. Die tema van “wonderwerke” is hier een moontlikheid. Hopelik sal hierdie studie (nogmaals) ‘n bydrae lewer tot ‘n byna vergete debat wat in 1787 deur J.P. Gabler begin is.
Thesis (Ph.D. (Old Testament Studies))--University of the Free State, 2014
Keywords: Jesus Christ -- Miracles; Moses (Biblical leader); Elijah (Biblical prophet); Miracles; Bible -- Theology